Pengaruh Kepatuhan Pajak, Kualitas Pelayanan Pajak dan Biaya Sanksi Kepatuhan Pajak terhadap Penerimaan Pajak Kendaraan Bermotor dengan Tax Amnesty sebagai Variabel Moderasi pada UPT Badan Pendapatan Daerah Wilayah Kabupaten Kupang - Lulan, Lodianus P.; Manafe, Henny A.; Perseveransa, M. E (Universitas Batanghari Jambi, 2024)
This research aims to determine the effect of tax compliance, tax service quality and tax compliance sanction costs on motor vehicle tax revenues with tax amnesty as a moderating variable at the Kupang Regency Regional Revenue Agency UPT. This research involved conducting a quantitative survey. The sample used as the main data source was 100 Kupang Regency taxpayers. Inferential statistical analysis is a type of data analysis method used in this research. The results of this research statistically found that taxpayer compliance does not have a significant influence on motor vehicle tax revenue. However, the quality of tax services and sanction fees have a positive and significant influence on motor vehicle tax revenues in the UPT activities of the Kupang Regency Regional Revenue Agency. Meanwhile, the tax amnesty variable as a moderating variable has an influence on motor vehicle tax revenues, but the tax amnesty variable is unable to moderate the influence of taxpayer compliance and compliance sanctions costs on motor vehicle tax revenues. The tax amnesty variable is only able to moderate the influence of service quality on motor vehicle tax revenues in the UPT activities of the Kupang Regency Regional Revenue Agency